If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v + -12 = -4 Reorder the terms: -12 + v = -4 Solving -12 + v = -4 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + v = -4 + 12 Combine like terms: -12 + 12 = 0 0 + v = -4 + 12 v = -4 + 12 Combine like terms: -4 + 12 = 8 v = 8 Simplifying v = 8
| (2x+1)=2 | | 2(a-8)+7=5(a-2)-4a-19 | | z^2+18z+62=0 | | z^2+182+62=0 | | (X^3-13x+12)/(x-3) | | -5/8y=-5 | | 9(x+3)=3(x+3) | | 1-4n=-n-2 | | x+5forx=-18 | | 4a-5b= | | 49Z+4=54 | | 7y^0= | | (6^3/9)+(18+10)^2 | | 14/5(3/10) | | K=13+5k | | -3=-2/3+v/3 | | 33+17=x-20 | | 8+10y+3y-12= | | -3=-2+v | | 441=x^2+20x | | 0=-1+n/10 | | 100x^2-1=99 | | 28=3n-2 | | 9k+8= | | 8C-5=35 | | 100p^2+9=90 | | 4a^2+9=-19 | | 64x^2=64 | | -7x-3=3-6x | | 3x^2/144=-2x/3 | | 3k+7= | | -10n-40=4n-12 |